ANALYSIS OF ASSESSMENT OF GUARANTEE IN THE PROVISION OF WORKING CAPITAL CREDIT IN PT. MANDIRI SULAWESI PEOPLE'S CREDIT BANK - Hafa, Abdul Rahim (Perpustakaan dan Penerbitan Unismuh Makassar, 2019)
The purpose of this study is to analyze the valuation of collateral in working capital loans at PT. Mandiri Rural Credit Bank. The analysis of the data used in this discussion is descriptive qualitative and quantitative analysis, which is an analysis that describes or describes the assessment of collateral for the granting of working capital loans at PT. Sulawesi Mandiri Rural Credit Bank and use analysis of market value and liquidation value to find out what valuation is used by PT. Sulawesi Rural Credit Bank Mandiri in assessing debtor guarantees. Based on the results of the research and discussion in the previous chapter, the authors can conclude that the assessment of collateral for the provision of working capital loans at PT. The Mandiri Sulawesi Rural Credit Bank is in accordance with the current system, namely the value of liquidation. which is where the value of liquidation is the most objective and safe value used by the bank.